Did the Early Church absolutely forbid remarriage after divorce? - David G. Hunter (Vergentis. Revista de Investigación de la Cátedra Internacional Conjunta Inocencio III, 2018)
The possibility to remarry in the Catholic Church is still a matter of intense debate, also in the Latin Church. The historical-juridical research about the discipline of remarriage in the pre-Augustine writings and tradition demonstrates that the teaching of the complete indissolubility of marriage wasn't accepted by everyone, not even in the Western Church. The comment of Ambrosiaster to the Pauline teaching, in fact, demonstrates that the possibility to remarry wasn’t always excluded, at least not until Augustin’s teaching became the dominant tradition in the West.